Design of Intelligent Embedded Data Acquisition and Storage System for Coal Mill Based on DSP - Shen, Hai (Recent Patents on Engineering, 2020)
Background: In order to better realize the real-time on-line monitoring of the working state of the coal mill and determine the status of the equipment used in the coal mill, the intelligent embedded system of the coal mill based on DSP was studied. Methods: Firstly, the working requirement of the coal mill and the task of data acquisition system have been briefly introduced, and the requirement of the overall embedded system design has been put forward. Then, the structure design was analysed including both hardware and software, and the embedded system design including digital signal processing, and data acquisition was completed. All patents related to intelligent embedded data acquisition and storage system are described in detail. Results: After that, the function test of the actual coal mill embedded system was carried out, which proved the practicability and reliability of the designed embedded system for coal mill and based on DSP. Conclusion: The embedded system improves the automation level of coal mill, and is of great significance to the on-line monitoring and research of large-scale machinery and equipment in the future.
Keywords: data acquisition